Nodal Metastases in Pediatric and Adult Acinic Cell Carcinoma of the Major Salivary Glands. (8th March 2022) - Dublin, Jared C.; Oliver, Jamie R.; Tam, Moses M.; Persky, Michael J.; Jacobson, Adam S.; Liu, Cheng; Hu, Kenneth S.; Vaezi, Alec E.; Morris, Luc G.T.; Givi, Babak
Abstract : Objective: Acinic cell carcinoma (AciCC) is a rare, usually low‐grade salivary malignancy. Evidence on rates of lymph node metastases (LNMs) is limited in pediatric patients and varies significantly (4%‐45%) in adults. We set out to determine and compare rates of LNMs in pediatric and adult AciCC and to analyze their impact on survival, using the National Cancer Database. Study Design: Historical cohort study. Setting: National Cancer Database. Methods: All AciCCs of the major salivary glands with complete clinical and pathologic nodal staging were selected between 2010 and 2016. Patient demographics, tumor characteristics, treatment, and survival were analyzed. Univariable and multivariable regression were performed to determine factors associated with LNMs and survival. Results: We identified 57 (4.6%) pediatric patients (<18 years) and 1192 (95.4%) adults with AciCC. Clinical LNMs were rare in pediatric patients (n < 10) and adults (n = 88, 7.4%). Occult LNMs were uncommon in pediatric patients (n < 5) and adults (n = 41, 4.6%). Three‐year overall survival for pediatric patients was 97.8%. Adults with LNM had worse 3‐year overall survival than those without (66.0% vs 96.3%, P <. 001). In multivariable regression, high‐grade disease (hazard ratio, 10.15 [95% CI, 5.60‐18.80]; P <. 001) and T3‐T4 tumors (hazard ratio, 2.80 [95% CI, 1.56‐4.97]; P <. 001) were associated with LNM in adult patients. Conclusion: LNMs in AciCC of the major salivary glands are rare in children and adults. However, high‐grade and T3‐T4 tumors are associated with an increased risk of LNM. LNM is associated with worse survival.